CORRELATION BETWEEN NECK CIRCUMFERENCE WITH BODY COMPOSITION AND BIOMARKERS IN NURSING PROFESSIONALS (Fiep Bulletin - online, 2014)
Background: Biomarkers and body circumferences can predict future risks to the cardiovascular health of individuals. Goals: To determine the correlation between neck circumference, body composition and inflammatory markers homocysteine, fibrinogen and C-reactive protein in nursing professionals. Methods: The authors conducted a cross-sectional descriptive, which was attended by 58 female nurses, aged between 18-69 years old, from a public hospital in Belém-PA. Anthropometric variables were evaluated such as weight, height, circumferences, breadths and laboratory tests. Results: Pearson's Rs indicated no significant associations between neck circumference and C-reactive protein biomarkers (r= -0.01, P=0.92), fibrinogen (r= -0.15, P=0, 25) and homocysteine (r=0.03, P=0.78), however, there were strong and significant correlations between neck circumference and anthropometric variables such as body mass index (r=0.78, P
Keywords: biomarkers; neck; body composition